International social work students in field education- considerations for supervision. Issue 6 (18th August 2022) - Zuchowski, Ines; Cleak, Helen; Cleaver, Mark
ABSTRACT: There is an increase of international students studying social work in Australia. Undertaking the compulsory field work component of social work studies can be particularly complex for international students, as they have to acquire an understanding of social work practice, knowledge and skills in a new cultural context. Prior research has highlighted the importance of supporting students and field educators to ensure successful quality learning experiences for international students in social work field education experiences. This paper reports on a subset of 35 international students who responded to a 2019 field education supervision survey in one Australian state, Queensland. The findings highlight that more international than domestic students are placed in placements with external supervision, that the overall the student cohort is younger than domestic students and that more international students reported longer supervision sessions. Despite field placements often being personally challenging international students rated their supervision experiences positively, and highlighted the opportunities it provided for support, learning and professional development. Students recognised that the process helped them understand concepts of critical reflection and an appreciation of the value of supervision and professional support for their ongoing professional development.